Social Security with Rational and Hyperbolic Consumers - Hans Fehr; Christian Habermann; Fabian Kindermann (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2006)
The present paper studies the role of social security in an economy populated by overlapping generations of individuals that have time-consistent or time-inconsistent preferences, face mortality and individual income risk, borrowing constraints as well as progressive income taxes. Our simulations start from an artificial equilibrium where social security is completely neutral. Next we introduce successively alternative deviations from neutrality in order to isolate the various economic effects of social security. The latter are mainly the insurance provision against mortality and income risk, the negative liquidity effects for young households and the provision of a commitment technology for present-biased hyperbolic consumers. Our simulations indicate that the positive effects of social security dominate the negative ones for a wide range of parameter combinations. For our central parametrization social security induces an overall welfare gain which amounts to roughly 1.5 percent of aggregate resources in the hyperbolic model and a welfare loss of about 0.5 percent of resources in the model with rational consumers.
Keywords: H55; J26; 330; social security; stochastic general equilibrium; hyperbolic consumers